The emerging female citizen : gender and enlightenment in Spain - Smith, Theresa Ann, 1971- (Berkeley [Calif.] ; London : University of California Press, 2006)
In analysing the meaning of women's presence in these diverse centres of the Enlightenment, Smith offers a new interpretation of the dynamic relationships among political discourse, social action, and gender ideologies.
Developing ideologies of citizenship -- The woman question -- Admitted equals: art and letters -- On equal terms?: membership in the economic society -- Enacting citizenship -- Negotiating a female public: writers and reformers -- Public works: female citizens as mothers and workers -- Between reason and passion: citizenship in translation.
Print version record.
Includes bibliographical references and index.
JSTOR
Keywords: Women -- Spain -- History -- 18th century; Sex role -- Spain -- History -- 18th century; Women -- Spain -- Intellectual life; Women -- Spain -- Social conditions; Feminism -- Spain -- History -- 18th century; Femmes -- Espagne -- Histoire -- 18e siècle.; Rôle selon le sexe -- Espagne -- Histoire -- 18e siècle.; Femmes -- Espagne -- Vie intellectuelle; Femmes -- Espagne -- Conditions sociales; Féminisme -- Espagne -- Histoire -- 18e siècle.; HISTORY -- Europe -- General; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Feminism; Sex role; Women; Women -- Intellectual life; Women -- Social conditions; Spain; 1700-1799; History